Election Crime in the Perspective of the Indonesian Democratic State (Law Research Review Quarterly, 2018)
The Election Law, which consists of six books, can be said to be the most comprehensive law on election arrangements to date. This comprehensive regulation is inseparable from the various polemics in the Election Law. One of the polemics in the Election Law is the election crime. Election crime arrangements in the Election Law have the potential to reduce democracy in Indonesia. The State of Indonesia is a democratic country and it has been stated indirectly in the 1945 Constitution. This means that the provisions of criminal acts contained in the Election Law must not conflict with a democratic state. The formulation of the problem in this article is how election crimes are in the perspective of Indonesia's democratic state and how the potential for election crimes threatens the democratic perspective of Indonesia's democratic state. The object of this research is the provision of criminal acts in the Election Law and the concept of the democratic state of Indonesia according to the 1945 Constitution. This research method is to use a qualitative research approach and type of normative juridical research. The results of this study are election criminal offenses in the perspective of the Indonesian democratic state and appropriate arrangements related to election criminal acts from the perspective of the democratic state of Indonesia. The conclusion of this research is that the criminal act of election can be enforced in Indonesia as long as it does not conflict with democracy in the State of Indonesia.